Value of the myocardial performance index in myocardial infarction. Issue 5 (14th April 2005) - Galiuto, L
Abstract : The myocardial performance index represents an easy and reproducible parameter of both systolic and diastolic left ventricular function for the risk stratification of patients following acute myocardial infarction